2015
DOI: 10.1136/jramc-2014-000394
|View full text |Cite
|
Sign up to set email alerts
|

Education and Ebola: initiating the cascade of emergency healthcare training

Abstract: In response to the 2014 Ebola virus outbreak in West Africa, the UK deployed a Joint Inter-Agency Task Force to Sierra Leone. As well as constructing Ebola treatment units, the force supported a rapidly upscaled mass programme of training for host nation healthcare workers in basic knowledge of Ebola and personal protective equipment. A bespoke training course was developed in collaboration with the WHO and other partners over a period of 2 weeks, taught to 119 trainers the following week, and then cascaded to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…Again, some good practices are identified that are crucial components of successful CMC. These include pre-existing relationships, early involvement of stakeholders and the use of liaisons to improve mutual trust and support for programmes 56–61. For example, during the West African Ebola crisis, the UK military training programme on the use of personal protective equipment was initiated with early engagement of local staff and handed over to a non-governmental organisation for a more long-term and sustainable execution 56.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, some good practices are identified that are crucial components of successful CMC. These include pre-existing relationships, early involvement of stakeholders and the use of liaisons to improve mutual trust and support for programmes 56–61. For example, during the West African Ebola crisis, the UK military training programme on the use of personal protective equipment was initiated with early engagement of local staff and handed over to a non-governmental organisation for a more long-term and sustainable execution 56.…”
Section: Resultsmentioning
confidence: 99%
“…Despite being trained to work in challenging contexts, military risk aversion and inflexibility on mission objectives has been frequently observed 1 64 66 67 71. Furthermore, language barriers, including the use of operational terminology, can create challenges in communication,57 58 65 72 as do differences in organisational cultures regarding authority, backgrounds and interests 57 60–62. The directness of military personnel does not remedy this situation,58 62 64 but instead, has resulted in growing aversion among civilian agencies 62…”
Section: Resultsmentioning
confidence: 99%
“…For knowledge evaluation, 101 studies [ 18 , 19 , 34 , 42 , 43 , 49 , 66 , 80 , 91 , 95 , 96 , 98 , 100 , 101 , 104 , 108 , 110 , 112 , 117 , 156 , 164 , 169 , 170 , 173 , 176 , 178 181 , 183 , 186 188 , 190 , 195 – 199 , 201 , 203 , 206 208 , 212 , 213 , 215 , 217 , 218 , 220 , 222 , 224 229 , 231 236 , 238 , 240 , 244 246 , 249 , 250 , 253 , …”
Section: Prominent Topic Areasunclassified
“…By the time of handover to the International Organisation for Migration in December 2014, the Training Academy had trained 4000 healthcare staff from across the country to WHO standards enabling them to more safely deliver care. 22 In Kerrytown, an Ebola Treatment Centre (ETC) had been constructed, co-located with the NGO Save the Children, and was receiving patients within six weeks of activation -the first in-country ETC dedicated to providing care to international and local healthcare workers infected with Ebola. The care provided included advanced techniques usually only available in critical care environments such as ultrasound-guided fluid management and specialised medications delivered via central venous lines.…”
Section: The Ebola Epidemic and Operation Gritrockmentioning
confidence: 99%